Neural Correlates of Group Versus Individual Problem Solving Revealed by fMRI - Shpurov, Ilya Yu.; Vlasova, Roza M.; Rumshiskaya, Alena D.; Rozovskaya, Renata I.; Mershina, Elena A.; Sinitsyn, Valentin E.; Pechenkova, Ekaterina V. (Frontiers in Human Neuroscience, 2020)
Group problem solving is a prototypical complex collective intellectual activity. Psychological research provides compelling evidence that problem solving in groups is both qualitatively and quantitatively different from doing so alone. However, the question of whether individual and collective problem solving involve the same neural substrate has not yet been addressed, mainly due to methodological limitations. In the current study, functional magnetic resonance imaging was performed to compare brain activation when participants solved Raven-like matrix problems in a small group and individually. In the group condition, the participant in the scanner was able to discuss the problem with other team members using a special communication device. In the individual condition, the participant was required to think aloud while solving the problem in the silent presence of the other team members. Greater activation was found in several brain regions during group problem solving, including the medial prefrontal cortex; lateral parietal, cingulate and retrosplenial cortices; and frontal and temporal poles. These areas have been identified as potential components of the so-called “social brain” on the basis of research using offline judgments of material related to socializing. Therefore, this study demonstrated the actual involvement of these regions in real-time social interactions, such as group problem solving. However, further connectivity analysis revealed that the social brain components are co-activated, but do not increase their coupling during cooperation as would be suggested for a holistic network. We suggest that the social mode of the brain may be described instead as a re-configuration of connectivity between basic networks, and we found decreased connectivity between the language and salience networks in the group compared to the individual condition. A control experiment showed that the findings from the main experiment cannot be entirely accounted for by discourse comprehension. Thus, the study demonstrates affordances provided by the presented new technique for neuroimaging the ‘group mind’, implementing the single-brain version of the second-person neuroscience approach.